Evaluation Report on District Industries Centre (DIC) Union Territory of Pondicherry - Planning Commission (Planning Commission, 1987)
The District Industries Centre Programme was launched in the country in 1978 with the primary objective of providing an integrated administrative framework at the district level which will shift the focal point of development of small scale and cottage industries from state capitals to District Headquarters and make available all the support and services needed by these industries under a single roof.
Programme Evaluation Organisation, Planning Commission, Government of India